Socioeconomic inequalities in health among elderly people in Taiwan: A life course perspective - Hsiao-Hsiao Tan; Yi-Chan Lee; Ya-Mei Chen; Tung-liang Chiang (PLoS ONE, 2025)
Background Individuals’ health could be well predicted through their lifetime trajectories. Those with greater socioeconomic advantages tend to exhibit better health and a slower rate of health decline as they age, and vice versa. Objective This study aims to investigate how health trajectory in old age is shaped by the accumulation of socioeconomic status (SES) across three life stages. Method The dataset used in this study is derived from the Taiwan Longitudinal Study on Aging (TLSA) conducted from 1989 to 2003, with 4,048 respondents aged 60 and older. A stratified analysis, utilizing Generalized Estimating Equations (GEE) models, is employed to investigate the interrelationships between SES across three life stages and the longitudinal patterns of three health outcomes. Result Of all the participants over the five waves, participants’ health declined with aging, while the proportion of higher SES among remaining individuals tended to increase. A gradient in health improvements is observed, corresponding to the accumulation of SES, even after adjusting for demographic factors and baseline health. Moreover, improvements in a single SES indicator are significantly associated with better health when controlling for the other two indicators (all p < 0.01). This indicates an independent effect of each SES indicator. Additionally, SES tends to be inherited from preceding statuses. The interaction among all three SES indicators cannot be overlooked when considering the association between SES and health. Conclusion Health outcomes are shaped progressively and independently by each SES factor, with these effects being reinforced by the cumulative nature of SES. Policies aimed at enhancing later-life health are better implemented in early life stages. However, it is never too late, as each SES at different life stages has its own effect and cannot be offset.